(untitled) (BioLaw Journal - Rivista di BioDiritto, 2026)
This paper investigates the hermeneutic challenges posed by technological acceleration, analyzing the evolution from the physical person to the “enhanced subject” and “digital subject”. By examining human enhancement practices and digital twins, the study highlights the crisis of traditional dogmatic and constitutional categories, including biodiversity protection under Art. 9 of the Constitution. Particular attention is paid to the complex quantification of damages resulting from the injury to “supra-normal” capacities, proposing the analogical application of differential damage. Finally, the article advocates for a “new legal humanism” capable of governing man-machine hybridization, balancing self-determination, progress, and human dignity.